Design of reconfigurable multiple element microstrip rectangular linear array antenna - Ali, M. T. (EMW Publishing, 2009)
This paper presents a reconfigurable multiple element microstrip rectangular linear array antenna integrated with radio frequency (RF) switches. The corporate feed design concept is used to excite the linear array antenna that consists of 8 elements of rectangular patches at 5.8 GHz. Two PIN diode switches were deployed at the feeding line to activate the two arrays of patches that are located on the left and right sides of the antenna structure. The behavior of the reconfigurable multiple element linear antenna array system has been investigated with respect to the beam shaping characteristic. The comparisons of the performance between two structures, with and without Wilkinson Power Divider (WPD) are discussed in this paper. Two different beam patterns were achieved through the reconfigurable antenna at different number of elements design that incorporates with PIN diode switches and modified WPD concept. The simulation and the measurement results for 4 and 8 elements array antenna structure are presented.